MICROSTRUCTURE AND MECHANICAL-PROPERTIES OF CORDIERITE CERAMICS TOUGHENED BY MONOCLINIC ZRO2 - OH, YJ; OH, TS; JUNG, HJ (CHAPMAN HALL LTD, 1991)
The effects of m-ZrO2 addition on the mechanical behaviour of the cordierite ceramics were studied. Below 10 vol % of m-ZrO2 content, zircon (ZrSiO4) was formed as a second phase at the expense of all m-ZrO2 due to the reaction between ZrO2 and silica in the cordierite. The sintered density was improved with ZrO2 addition through glass phase formation along grain boundaries, and maximum sinterability was obtained at 4.6 vol % m-ZrO2. When sintered at 1300-degrees-C for 4 h, the flexural strength at 4.6 vol% ZrO2 was 190 MPa, compared with 55 MPa for the pure cordierite. Fracture toughness was gradually enhanced from 1.75 M Pa m1/2 to 2.4 M Pa m1/2 with m-ZrO2 addition up to 10 vol %, which could be explained partly by thermal expansion mismatch between cordierite and the second-phase ZrSiO4 and partly by crack deflection at the cordierite-ZrSiO4 interfaces.
Keywords: FRACTURE-TOUGHNESS; THERMAL-EXPANSION; ZIRCONIA; COMPOSITES